Bioactive glass based scaffolds coated with gelatin for the sustained release of icariin. - Reiter, Theresa; Panick, Tanja; Schuhladen, Katharina; Roether, Judith; Hum, Jasmin; Boccaccini, Aldo R. (Bioactive Materials, 2019)
Gelatin-coated, 3D sponge-like scaffolds based on 45S5 bioactive glass were produced using the foam replication technique. Compressive strength tests of gelatin-coated samples compared to uncoated scaffolds showed significant strengthening and toughening effects of the gelatin coating with compressive strength values in the range of cortical bone. Additionally, the crosslinked gelatin network (using either caffeic acid or N-(3-Dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC)/N-hxdroxysuccinimide (NHS) as crosslinking agent) was shown to be a suitable candidate for the sustained release of the bioactive molecule icariin. Concerning bioactivity of the produced scaffolds, characterization by FTIR and SEM indicated the formation of hydroxyapatite (HA) in all samples after immersion in simulated body fluid (SBF) for 14 days, highlighting the favorable combination of mechanical robustness, bioactivity and drug delivery capability of this new type of scaffolds.

BIOACTIVE GLASSES AND THE IMMUNE SYSTEM: RECENT FINDINGS AND FUTURE PERSPECTIVES - Boccaccini, Aldo R.; Schuhladen, Katharina; Steinkasserer, Alexander; Zinser, Elisabeth (TISSUE ENGINEERING PART A, 2022)
CRIS-Team WoS Importer:2022-08-12

Bioactive glasses as angiogenic agents for tissue engineering - Schuhladen, Katharina; Boccaccini, Aldo R. (Encyclopedia of Tissue Engineering and Regenerative Medicine, 2019)
Angiogenesis is controlled by several regulators and is essential for the success of any healing or regenerative process in the human body. By using bioactive glasses (BGs) of varying compositions, angiogenesis and its regulators can be effective stimulated. The angiogenic effect of BGs is mainly the result of the release of biologically active ions during their immersion in the human body. By fine-tuning the compositions of BGs, the release kinetics of ions can be controlled and specific cellular responses and tissue reactions can be achieved. This article discusses BGs of different compositions in their applications in vascularization strategies for tissue engineering.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Angiogenesis; Bioactive glasses; Borate glasses; Ion concentration; Ion doping; Ion release; Mesoporous glasses; Regulators of angiogenesis; Silicate glasses; Therapeutic ions; Tissue engineering; Vascularization; VEGF

Bioactive glasses meet phytotherapeutics: The potential of natural herbal medicines to extend the functionality of bioactive glasses - Schuhladen, Katharina; Roether, Judith; Boccaccini, Aldo R. (Biomaterials, 2019)
Herbal medicine, the use of plants or plant extracts with known beneficial biological effects to treat and/or prevent diverse health disorders, has been known for thousands of years. After their replacement by synthetic drugs in the beginning of the 20th century, plant derived therapeutic agents have been recently attaining more attention again. Phytotherapeutics, which can be extracted from a wide range of different herbal plants, are believed to have a broad spectrum of therapeutic effects and less negative side effects than synthetic drugs. On the other hand, it is often difficult to prove the therapeutic effect of herbal drugs due to their chemical complexity. In the last decade, research has focused increasingly on the relatively new concept of the combination of herbal drugs with modern engineered biomaterials in order to achieve synergy of their therapeutic effects. Even if several studies based on this concept have been published, no systematic overview of the performed investigations and their results is available. In this context, this review focuses on the combination of phytotherapeutics with bioactive glasses (BGs), which are bioactive and biodegradable materials capable of releasing biologically active ions being suitable for several applications as bone substituting and replacing materials as well as in the regeneration of soft and hard tissue. The literature search was carried out using the WEB OF SCIENCE® and SCOPUS® databases using a combination of relevant keywords. Besides giving an overview of the research done in the last years and summarizing the results obtained in those studies, the possible synergistic effects of herbal drugs in combination with BGs are critically discussed, and potential health risks are overviewed. Of all plant-derived drugs investigated so far, the coumarin family appears to be the one that has been most widely combined with BGs showing beneficial outcomes. Overall, the analysis of the literature has revealed the great potential of this organic-inorganic multi-functional system approach as an advantageous alternative to conventional medicine in several applications, but also highlights the need for more systematic in vivo studies to evaluate the effective time and dose dependent combined effects of BGs and phytotherapeutic agents.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Bioactive glass; Composite; Drug delivery; Phytotherapeutics; Synergistic effect

Bioactive glass variants for tissue engineering: From the macro- to the nanoscale - Schuhladen, Katharina; Boccaccini, Aldo R. (Elsevier, 2020)
Bioactive glass (BG), a typical example for a third-generation biomaterial, shows great success in the regeneration, repair, and replacement of damaged tissue, due its ability to release therapeutic ions and to form an apatite layer during dissolution in physiological fluids. Since the development of the first bioactive glass 50years ago, different glass compositions and fabrication methods have led to the development of a wide variety of bioactive glasses, some of them being highly relevant for tissue engineering applications, both hard and soft tissues. With ongoing development of advanced fabrication methods, a reduction in bioactive glass dimensions (e.g., particle size) from macroscopic to nanosize has been achieved. This chapter presents a summary of achievements of 50years of research on bioactive glasses for tissue engineering and drug delivery applications highlighting the three kinds of bioactive glasses linking applications in the field, namely, melt-derived, sol-gel-derived, and mesoporous BGs.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Bioactive glasses; Drug delivery; Ion release; Scaffolds; Sol-gel; Tissue engineering

Borate and silicate bioactive glass coatings prepared by nanosecond pulsed laser deposition - Rau, Julietta V.; De Bonis, Angela; Curcio, Mariangela; Schuhladen, Katharina; Barbaro, Katia; De Bellis, Giovanni; Teghil, Roberto; Boccaccini, Aldo R. (Coatings, 2020)
Silicate (13-93) and borate (13-93-B3) bioactive glass coatings were successfully deposited on titanium using the nanosecond Pulsed Laser Deposition technique. The coatings’ microstructural characteristics, compositions and morphologies were examined by a number of physico-chemical techniques. The deposited coatings retain the same functional groups of the targets, are a few microns thick, amorphous, compact and crack free. Their surface is characterized by the presence of micrometric and nanometric particles. The surface topography, investigated by Atomic Force Microscopy, is characterized by spherical or ellipsoidal particles of the 0.2–3 µm size range for the 13-93 silicate bioactive glass film and of the 0.1–1 µm range for the 13-93-B3 borate bioactive glass coating. Equine adipose tissue-derived mesenchymal stem cells (ADMSCs) were applied for biological tests and the osteogenic differentiation activity of cells on the deposited coatings was studied after ADMSCs growth in osteogenic medium and staining with Alizarin Red. Cytocompatibility and osteogenic differentiation tests have shown that thin films retain the biocompatibility properties of the target silicate and borate glass, respectively. On the other hand, no antibacterial activity of the borate glass films was observed, suggesting that ion doping is advisable to inhibit bacterial growth on the surface of borate glass thin films.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Antibacterial activity; Borate bioactive glass coatings; Cytocompatibility; Equine adipose tissue-derived stem cells; Nanosecond pulsed laser deposition; Silicate bioactive glass coatings

Calorimetric approach to assess the apatite-forming capacity of bioactive glasses - Zine Elabidine, Mohamed; Cherbib, Mohamed Atef; Khattech, Ismail; Bechrifa, Ali; Schuhladen, Katharina; Brauer, Delia S.; Boccaccini, Aldo R. (Journal of Non-Crystalline Solids, 2020)
This paper investigates a new microcalorimetric approach to assess the capacity of bioactive glasses, to form hydroxyapatite during immersion in physiological fluids. Three silicate glasses were selected namely 45S5 (46.1SiO2-2.6P2O5-26.9CaO-24.4Na2O; mol%), F0 (46.1SiO2-2.6P2O5-37.6CaO-6.8Na2O-6.8K2O; mol%), and F3 (44.8SiO2-2.5P2O5-36.5CaO-6.6Na2O-6.6K2O-3.0CaF2; mol%), synthesized by a melt-quench route and studied initially using electron microscopy. The hydroxyapatite formation of samples immersed in simulated body fluid (SBF) was monitored using X-ray diffraction and Infrared spectroscopy. The microcalorimetric investigations were conducted by observing, over seven days, the thermochemical behavior of glasses in SBF at 37°C and by measuring the heat of acidic dissolution of treated and untreated samples in SBF. The results showed that the samples with the higher capacity to form apatites also present the higher heat variation from day-to-day, with 45S5 presenting the highest heat difference recorded in both experiments. These analyses led to the quantification of the calcium phosphate formed for each bioactive glass composition.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Apatite; Bioactive glass; Bioactivity; Microcalorimetry; Thermochemistry

Comparison of the influence of 45s5 and Cu-containing 45s5 bioactive glass (BG) on the biological properties of novel Polyhydroxyalkanoate (PHA)/BG composites - Schuhladen, Katharina; Lukasiewicz, Barbara; Basnett, Pooja; Roy, Ipsita; Boccaccini, Aldo R. (Materials, 2020)
Polyhydroxyalkanoates (PHAs), due to their biodegradable and biocompatible nature and their ability to be formed in complex structures, are excellent candidates for fabricating scaffolds used in tissue engineering. By introducing inorganic compounds, such as bioactive glasses (BGs), the bioactive properties of PHAs can be further improved. In addition to their outstanding bioactivity, BGs can be additionally doped with biological ions, which in turn extend the functionality of the BG-PHA composite. Here, different PHAs were combined with 45S5 BG, which was additionally doped with copper in order to introduce antibacterial and angiogenic properties. The resulting composite was used to produce scaffolds by the salt leaching technique. By performing indirect cell biology tests using stromal cells, a dose-depending effect of the dissolution products released from the BG-PHA scaffolds could be found. In low concentrations, no toxic effect was found. Moreover, in higher concentrations, a minor reduction of cell viability combined with a major increase in VEGF release was measured. This result indicates that the fabricated composite scaffolds are suitable candidates for applications in soft and hard tissue engineering. However, more in-depth studies are necessary to fully understand the release kinetics and the resulting long-term effects of the BG-PHA composites.
CRIS-Team Scopus Importer:2020-07-03
Keywords: Bioactive glass; Copper; Polyhydroxyalkanoates; Scaffolds; Tissue engineering

Cu, Zn doped borate bioactive glasses: antibacterial efficacy and dose-dependent in vitro modulation of murine dendritic cells - Schuhladen, Katharina; Stich, Lena; Schmidt, Jochen; Steinkasserer, Alexander; Boccaccini, Aldo R.; Zinser, Elisabeth (Biomaterials Science, 2020)
Among emerging biomaterials, bioactive glasses (BGs) are being widely explored for various applications in tissue engineering. However, the effects of BGs (in particular BG ionic dissolution products) on immune cells and specifically on dendritic cells (DCs), which are the most potent antigen-presenting cells of the immune system, have not been previously investigated in detail. Such interactions between BGs and DCs must be assessed as a novel biocompatibility criterion for biomaterials, since, with the increased application possibilities of BGs, the modulation of the immune system may induce potential complications and undesired side effects. Indeed, the effects of BG exposure on specific immune cells are not well understood. Thus, in this study we investigated, for the first time, the effect of borate BGs doped with biologically active ions on specific immune cells, such as DCs and we further investigated the antibacterial properties of these borate BGs. The compositions of the borate BGs (B3) were based on the well-known 13-93 (silicate) composition by replacing silica with boron trioxide and by adding copper (3 wt%) and/or zinc (1 wt%). By performing an agar diffusion test, the antibacterial effect depending on the compositions of the borate BGs could be proved. Furthermore we found a dose-dependent immune modulation of DCs after treatment with borate BGs, especially when the borate BGs contained Zn and/or Cu. Depending on the ion concentration and the rise in pH, the phenotype and function of DCs were modified. While at low doses B3 and Zn-doped B3 BGs had no impact on DC viability, Cu containing BGs strongly affected cell viability. Furthermore, the surface expression of DC-specific activation markers, such as the major histocompatibility complex (MHC)-II, CD86 and CD80, was modulated. In addition, also DC mediated T-cell proliferation was remarkably reduced when treated with high doses of B3-Cu and B3-Cu-Zn BGs. Interestingly, the release of inflammatory cytokines increased after incubation with B3 and B3-Zn BGs compared to mock-treated DCs. Considering the essential role of DCs in the modulation and regulation of immune responses, these findings provide first evidence of phenotypic and functional consequences regarding the exposure of DCs to BGs in vitro.
CRIS-Team Scopus Importer:2020-04-28

Development of multifunctional wound dressings by using newly designed ion-doped borosilicate and borate bioactive glasses - Schuhladen, Katharina (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)

Dissolution of borate and borosilicate bioactive glasses and the influence of ion (Zn, Cu) doping in different solutions - Schuhladen, Katharina; Wang, Xiaoju; Hupa, Leena; Boccaccini, Aldo R. (Journal of Non-Crystalline Solids, 2018)
Keywords: Borosilicate glass; Copper; Bioactivity; Borate; Zinc; Dynamic dissolution; Lactic acid; Bioactive glasses

Effect of buffer in simulated body fluid on morphology and crystallinity of hydroxyapatite precipitated on 45S5 bioactive glass-derived glass–ceramic scaffolds: comparison of Good's buffer systems and TRIS - Horkavcová, D.; Stříbny, A.; Schuhladen, Katharina; Bezdička, P.; Boccaccini, Aldo R.; Rohanová, D. (Materials Today Chemistry, 2021)
In vitro tests that verify the ability of a material to form bone-like apatite precipitated (HAp) use a solution that imitates the inorganic part of blood plasma, simulated body fluid (SBF). During such tests, it is necessary to maintain a neutral pH, for which purpose the International Standards Organization recommends the TRIS (tris(hydroxymethyl)aminomethane) buffer (ISO 23,317:2014). To do this, TRIS buffer must remain inert, but, as we have previously reported, TRIS interacts with highly bioreactive materials (such as 45S5 Bioglass-derived scaffolds), thereby accelerating scaffold dissolution. In the search for an alternative to TRIS, we have also recently published results for the 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES) and 3-(N-morpholino) propanesulfonic acid (MOPS) buffers, which were also unable to maintain a neutral pH in SBF. Thus, we here continue our search for a more suitable Good's buffer by comparing BES (N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonic acid) and TES (2-[(2-hydroxy-1,1-bis(hydroxymethyl) ethyl) amino] ethanesulfonic acid) with TRIS. 45S5-derived glass–ceramic scaffolds were tested under static–dynamic conditions for bone-like apatite formation using SBF + BES and SBF + TES solutions. The pH measurements, leachate analysis [atomic absorption spectrophotometry (AAS) (Ca2+, SiIV), UltraViolet-Visible (UV-VIS) spectrophotometry (PO4)3−], and scaffold analysis [X-Ray powder diffraction analysis (XRD), X-ray fluorescent analysis (XRF), scanning electron microscopy (SEM)/energy dispersive spectroscopy (EDS), Brunauer.Emmett.Teller specific surface area analysis (BET)] all showed that both BES and TES quickly interacted with the tested material. Moreover, the kinetics of the glass–ceramic dissolution affected the crystallinity and morphology of the precipitated HAp. Based on our previous results and the present data, it appears that Good's buffers are not suitable for the in vitro testing of bioactivity of highly bioreactive materials.
CRIS-Team Scopus Importer:2021-08-06
Keywords: BES buffer; Bioactive high porous material; In vitro test; SBF; TES buffer

Electrophoretic Deposition of Bioadaptive Drug Delivery Coatings on Magnesium Alloy for Bone Repair - Qi, Hongfei; Heise, Svenja; Zhou, Juncen; Schuhladen, Katharina; Yang, Yuyun; Cui, Ning; Dong, Rongxin; Virtanen, Sannakaisa; Chen, Qiang; Boccaccini, Aldo R.; Lu, Tingli (ACS Applied Materials and Interfaces, 2019)
Biodegradable polymer coatings on magnesium alloys are attractive, as they can provide corrosion resistance as well as additional functions for biomedical applications, e.g., drug delivery. A gelatin nanospheres/chitosan (GNs/CTS) composite coating on WE43 substrate was fabricated by electrophoretic deposition with simvastatin (SIM) loaded into the GNs. Apart from a sustained drug release over 28 days, an anticorrosion behavior of the coated WE43 substrates was confirmed by electrochemical tests. Both the degradation and corrosion rates of the coated substrate were significantly minimized in contrast to bare WE43. The cytocompatibility of the coated samples was analyzed both quantitatively and qualitatively. Additionally, the osteogenic differentiation of MC3T3El cells on SIM-containing coatings was assessed by measuring the expression of osteogenic genes and related proteins, alkaline phosphatase (ALP) activity, and extracellular matrix mineralization, showing that the SIM-loaded composite coating could upregulate the expression of osteogenic genes and related proteins, promote ALP activity, and enhance extracellular matrix mineralization. In summary, the SIM-loaded GNs/CTS composite coatings were able to enhance the corrosion resistance of the WE43 substrate and promote osteogenic activity, thus demonstrating a promising coating system for modifying the surface of magnesium alloys targeted for orthopedic applications.
CRIS-Team WoS Importer:2019-03-20

Electrospun PCL/PGS composite fibers incorporating bioactive glass particles for soft tissue engineering applications - Luginina, Marina; Schuhladen, Katharina; Orrú, Roberto; Cao, Giacomo; Boccaccini, Aldo R.; Liverani, Liliana (Nanomaterials, 2020)
Poly(glycerol-sebacate) (PGS) and poly(epsilon caprolactone) (PCL) have been widely investigated for biomedical applications in combination with the electrospinning process. Among others, one advantage of this blend is its suitability to be processed with benign solvents for electrospinning. In this work, the suitability of PGS/PCL polymers for the fabrication of composite fibers incorporating bioactive glass (BG) particles was investigated. Composite electrospun fibers containing silicate or borosilicate glass particles (13-93 and 13-93BS, respectively) were obtained and characterized. Neat PCL and PCL composite electrospun fibers were used as control to investigate the possible effect of the presence of PGS and the influence of the bioactive glass particles. In fact, with the addition of PGS an increase in the average fiber diameter was observed, while in all the composite fibers, the presence of BG particles induced an increase in the fiber diameter distribution, without changing significantly the average fiber diameter. Results confirmed that the blended fibers are hydrophilic, while the addition of BG particles does not affect fiber wettability. Degradation test and acellular bioactivity test highlight the release of the BG particles from all composite fibers, relevant for all applications related to therapeutic ion release, i.e., wound healing. Because of weak interface between the incorporated BG particles and the polymeric fibers, mechanical properties were not improved in the composite fibers. Promising results were obtained from preliminary biological tests for potential use of the developed mats for soft tissue engineering applications.
CRIS-Team Scopus Importer:2020-06-23
Keywords: Benign solvents; Bioactive glass; Composite fibers; Electrospinning; Poly(glycerol-sebacate)

Gelatin coating increases in vivo bone formation capacity of three-dimensional 45S5 bioactive glass-based crystalline scaffolds - Westhauser, Fabian; Senger, Anne-Sophie; Obert, David; Ciraldo, Francesca; Schuhladen, Katharina; Schmidmaier, Gerhard; Moghaddam, Arash; Boccaccini, Aldo R. (Journal of Tissue Engineering and Regenerative Medicine, 2019)
Recent studies have demonstrated that surface characteristics, porosity, and mechanical strength of three-dimensional 45S5-type bioactive glass (BG)-based scaffolds are directly correlated with osteogenic properties. Three-dimensional BG-based scaffolds obtained from maritime natural sponges (MNSs) as sacrificial templates exhibit the required morphological properties; however, no in vivo data about the osteogenic features are available. In this study, uncoated (Group A) and gelatin-coated (Group B) crystalline MNS-obtained BG-based scaffolds were evaluated mechanically and seeded with human mesenchymal stem cells prior to subcutaneous implantation in immunodeficient mice. Before implantation and after explantation, micro-computed tomography scans were conducted, and scaffolds were finally subjected to histomorphometry. Scaffolds of both groups showed bone formation. However, Group B scaffolds performed distinctly better as indicated by a significant increase in scaffold volume (8.95%, p = 0.039) over the implantation period compared with a nonsignificant increase of 5.26% in Group A scaffolds in micro-computed tomography analysis. Furthermore, percentage bone area was 10.33% (+/- 1.18%) in the Group B scaffolds, which was significantly (p = 0.007) higher compared with the 8.53% (+/- 0.77%) in the Group A scaffolds in histomorphometry. Compressive strength was enhanced significantly by gelatin coating (9 +/- 2 vs. 4 +/- 1 MPa; p = 0.029). The presence of gelatin on the remnant parts was verified by scanning electron microscopy and X-ray spectroscopy, demonstrating the coatings' resilience. MNS-obtained BG-based scaffolds were thus confirmed to exhibit osteogenic properties in vivo that can significantly be enhanced by gelatin coating.
CRIS-Team WoS Importer:2019-03-15

Highly porous polymer-derived bioceramics based on a complex hardystonite solid solution - Elsayed, Hamada; Secco, Michele; Zorzi, Federico; Schuhladen, Katharina; Detsch, Rainer; Boccaccini, Aldo R.; Bernardo, Enrico (Materials, 2019)
Highly porous bioceramics, based on a complex hardystonite solid solution, were developed fromsilicone resins and micro-sized oxide fillers fired in air at 950 °C. Besides CaO, SrO, MgO, and ZnO precursors, and the commercial embedded silicone resins, calcium borate was essential in providing the liquid phase upon firing and favouring the formation of an unprecedented hardystonite solid solution, corresponding to the formula (Ca0.70Sr0.30)2(Zn0.72Mg0.15Si0.13) (Si0.85B0.15)2O7. Silicone-filler mixtures could be used in the form of thick pastes for direct ink writing of reticulated scaffolds or for direct foaming. The latter shaping option benefited from the use of hydrated calcium borate, which underwent dehydration, with water vapour release, at a low temperature (420 °C). Both scaffolds and foams confirmed the already-obtained phase assemblage, after firing, and exhibited remarkable strength-to-density ratios. Finally, preliminary cell tests excluded any cytotoxicity that could be derived from the formation of a boro-silicate glassy phase.
CRIS-Team Scopus Importer:2019-12-13
Keywords: 3D printed scaffolds; Biosilicate ceramics; Direct ink writing (DIW); Foams; Hardystonite; Polymer derived ceramics (PDCs)

Influence of the replacement of silica by boron trioxide on the properties of bioactive glass scaffolds - Schuhladen, Katharina; Pantulap, Usanee; Engel, Kristin; Jeleń, Piotr; Olejniczak, Zbigniew; Hupa, Leena; Sitarz, Maciej; Boccaccini, Aldo R. (International Journal of Applied Glass Science, 2021)
The dissolution properties and bioactivity of bioactive glasses (BGs) are mainly determined by their composition and glass network structure. Silicate BGs are arguable the most popular representatives of BGs. However, borate BGs have gained increasing interest due to their faster degradation rate. By adding boron trioxide in the silicate network, borosilicate BGs can be fabricated with controlled degradation rates. Since the kind and amount of network former determines the resulting BG properties, the aim of this study was to examine the glass structure of silicate, borosilicate and borate BGs. Also, the effect of changing the network former on the ability to fabricate BG scaffolds by the foam replica method was investigated. The resulting silicate, borosilicate, and borate scaffolds were further examined on their chemical, morphological, mechanical, and bioactive properties. Structural analyses showed that the introduction of boron trioxide into silicate BGs leads to the depolymerization of the silicate network. Accordingly, the ion release profile and the ability to form hydroxyapatite of the different scaffolds were affected. Thus, this study shows that tailored BG compositions with case-specific properties can be designed and used to fabricate 3D scaffolds for potential use in bone tissue engineering.
CRIS-Team Scopus Importer:2021-04-09
Keywords: bioactive glass; bioactivity; borate; borosilicate; scaffolds; structural analyses

Interaction of MOPS buffer with glass-ceramic scaffold: Effect of (PO4)(3-) ions in SBF on kinetics and morphology of formatted hydroxyapatite - Horkavcova, Diana; Rohanova, Dana; Stribny, Adam; Schuhladen, Katharina; Boccaccini, Aldo R.; Bezdicka, Petr (Journal of Biomedical Materials Research Part B: Applied Biomaterials, 2019)
The international standard ISO 23317:2014 for the in vitro testing of inorganic biomaterials in simulated body fluid (SBF) uses TRIS buffer to maintain neutral pH. In our previous papers, we investigated the interaction of a glass-ceramic scaffold with TRIS and HEPES buffers. Both of them speeded up glass-ceramic dissolution and hydroxyapatite (HAp) precipitation, thereby demonstrating their unsuitability for the in vitro testing of highly reactive biomaterials. In this article, we tested MOPS buffer (3-[N-morpholino] propanesulfonic acid), another amino acid from the group of "Goods buffers". A highly reactive glass-ceramic scaffold (derived from Bioglass (R)) was exposed to SBF under static-dynamic conditions for 13/15 days. The kinetics and morphology of the newly precipitated HAp were studied using two different concentrations of (PO4)(3-) ions in SBF. The pH value and the Si-IV, Ca2+, and (PO4)(3-) concentrations in the SBF leachate samples were measured every day (AAS, spectrophotometry). The glass-ceramic scaffold was monitored by SEM/EDS, XRD, WD-XRF, and BET before and after 1, 3, 7, 11, and 13/15 days of exposure. As in the case of TRIS and HEPES, the preferential dissolution of the glass-ceramic crystalline phase (Combeite) was observed, but less intensively. The lower concentration of (PO4)(3-) ions slowed down the kinetics of HAp precipitation, thereby causing the disintegration of the scaffold structure. This phenomenon shows that the HAp phase was predominately generated by the presence of (PO4)(3-) ions in the SBF, not in the glass-ceramic material. Irrespective of this, MOPS buffer is not suitable for the maintenance of pH in SBF.
CRIS-Team WoS Importer:2019-12-27

Manuka honey and bioactive glass impart methylcellulose foams with antibacterial effects for wound-healing applications - Schuhladen, Katharina; Mukoo, Pratishtha; Liverani, Liliana; Nescakova, Zuzana; Boccaccini, Aldo R. (Biomedical Materials, 2020)
Wound dressings able to deliver topically bioactive molecules represent a new generation of wound-regeneration therapies. In this article, foams based on methylcellulose cross-linked with Manuka honey were used as a platform to deliver borate bioactive glass particles doped additionally with copper. Borate bioactive glasses are of great interest in wound-healing applications due to a combination of favorable features, such as angiogenic and antibacterial properties. The multifunctional composite providing the dual effect of the bioactive glass and Manuka honey was produced by freeze-drying, and the resulting foams exhibit suitable morphology characterized by high porosity. Moreover, the performed tests showed improved wettability and mechanical performance with the addition of bioactive glass particles. Dissolution studies using simulated body fluid and cell biology tests using relevant skin cells further proved the excellent bioactivity and positive effects of the foams on cell proliferation and migration. Most interestingly, by the dual release of Manuka honey and ions from the copper-doped bioactive glass, an antibacterial effect againstE. coliandS. aureuswas achieved. Therefore, the multifunctional foams showed promising outcomes as potential wound dressings for the treatment of infected wounds.
CRIS-Team WoS Importer:2020-10-16

Production of a novel poly(ɛ-caprolactone)-methylcellulose electrospun wound dressing by incorporating bioactive glass and Manuka honey - Schuhladen, Katharina; Vakamulla Raghu, Swathi Naidu; Liverani, Liliana; Neščáková, Zuzana; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part B: Applied Biomaterials, 2020)
Wound dressings produced by electrospinning exhibit a fibrous structure close to the one of the extracellular matrix of the skin. In this article, electrospinning was used to fabricate fiber mats based on the well-known biopolymers poly(ɛ-caprolactone) (PCL) and methylcellulose (MC) using benign solvents. The blend fiber mats were cross-linked using Manuka honey and additionally used as a biodegradable platform to deliver bioactive glass particles. It was hypothesized that a dual therapeutic effect can be achieved by combining Manuka honey and bioactive glass. Morphological and chemical examinations confirmed the successful production of submicrometric PCL-MC fiber mats containing Manuka honey and bioactive glass particles. The multifunctional fiber mats exhibited improved wettability and suitable mechanical properties (ultimate tensile strength of 3–5 MPa). By performing dissolution tests using simulated body fluid, the improved bioactivity of the fiber mats by the addition of bioactive glass was confirmed. Additionally, cell biology tests using human dermal fibroblasts and human keratinocytes-like HaCaT cells showed the potential of the fabricated composite fiber mats to be used as wound dressing, specially due to the ability to support wound closure influenced by the presence of bioactive glass. Moreover, based on the results of the antibacterial tests, it is apparent that an optimization of the electrospun fiber mats is required to develop suitable wound dressing for the treatment of infected wounds.
CRIS-Team Scopus Importer:2020-07-31
Keywords: bioactive glass; electrospinning; Manuka honey; methylcellulose; wound healing

Sol-gel coatings incorporating borosilicate bioactive glass enhance anti corrosive and surface performance of stainless steel implants - Balestriere, M. A.; Schuhladen, Katharina; Herrera Seitz, K.; Boccaccini, Aldo R.; Cere, S. M.; Ballarre, J. (Journal of Electroanalytical Chemistry, 2020)
Metals are the most used materials as orthopaedic or dental implants due to their excellent mechanical properties. Stainless steel is one of the most commonly used materials based on its excellent mechanical properties and low costs compared with other metals, e.g. titanium alloys. In developing countries it is still one of the most used materials for temporary devices like bone plates and fixation screws and for permanent orthopaedic implants. However, stainless steel does not have good anticorrosive and bioactive surface properties in physiological media in comparison to other metals: stainless steel is not able to create a natural bonding with bone and might release corrosion products that could finally end in the removal of the implant. A promising approach to avoid those effects is to protect the implant with a functional coating, which additionally may have antibacterial properties. In this work, three kinds of bioactive glass particles (silicate, borosilicate and copper-doped borosilicate) were added as a second phase to a hybrid organic-inorganic silica based sol-gel made coating, with the aim of improving the surface properties of stainless steel as implant material. Chemical composition of the particles and coatings as well as the bioactive and anti-corrosive behaviour of the generated coating systems were analysed by Fourier Transformed Infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and by electrochemical tests. After 14 days of immersion in simulated body fluid solution, the particles contained in the coatings presented a slow dissolution, generating phosphate-rich deposits (first insight of bioactivity) and enhancing the electrochemical response.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Bioactivity; Corrosion protection; Cu-borosilicate bioactive glass; Sol-gel; Stainless steel

The effect of borate bioactive glass on the printability of methylcellulose-manuka honey hydrogels - Schuhladen, Katharina; Bednarzig, Vera; Rembold, Nadine; Boccaccini, Aldo R. (Journal of Materials Research, 2021)
Abstract: 3D printing offers the possibility to generate complex and individualized constructs (scaffolds) for applications in tissue engineering. This is viable by using suitable inks based on advanced biomaterials. Methylcellulose (MC), a highly biocompatible biomaterial, can be combined with manuka honey (H) to fabricate a thermo-sensitive hydrogel. Besides providing favorable biological effects, H can also be used as a natural cross-linking agent. Furthermore, the addition of bioactive glass (BG) to the ink could improve its mechanical and bioactive properties. In this study, a composite based on MC as matrix incorporating H and particulate borate BG as filler, was investigated as ink for 3D printing. Besides the improvement of the inks’ printability owing to the addition of BG, the printed scaffolds exhibited suitable swelling behavior and mechanical properties. Moreover, cell biology tests demonstrated the potential of the composite for biofabrication and applications in tissue engineering, which should be further explored. Graphic abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2021-06-18
Keywords: 3D printing; Additive manufacturing; Biomaterial; Porosity